PHYSICO-CHEMICAL PROPERTIES OF RAT PLASMA LIPOPROTEINS: INFLUENCES OF SYMPATHETIC AND PARASYMPATHETIC LIVER DENERVATION, PARTIAL HEPATECTOMY AND INTRAPORTAL INTRODUCTION OF ATROPIN - N. S. Parfenova; A. A. Kuznetsov (Российский кардиологический журнал, 2000)
Physical-chemical properties of very low density (VLDL) and two forms of high density lipoproteins (LP) - apo E-rich HDL and apo A-rich HDL in rat blood plasma after sympathetic and parasympathetic denervation of the liver, partial hepatectomy and intraportal atropine administration were investigated. Surface potential of VLDL and E-HDL in all experimental groups was significantly lower than in sham operated controls, but the most pronounced decrease was after intraportal atropine administration and in 7 days after partial hepatectomy. In A-HDL this parameter was essentially the same. VLDL and E-HDL particle radius significantly decreased after 70% hepatectomy and intraportal atropine administration, was slightly lower in 7 days after section of splanchnic nerves and vagotomy and was invariable in the case of A-HDL. VLDL and A-HDL lipid microviscosity increased after sympathetic denervation, partial hepatectomy and vagotomy. The degree of increase for VLDL under such conditions was higher than for A-HDL. As to E-HDL this parameter did not change. Percent of protein in water equipment in VLDL and E-HDL was greater after vagotomy and atropine administration and did not change in case of bilateral section of splanchnic nerves and hepatectomy. In A-HDL, this parameter was constant.As all these parameters reflect the LP assembling, structure and transformation, our results confirm the suggestion that autonomic neuronal factors influence the LP production, acting on post-transcriptional processes.